Underwater chemical denudation expressions of the Rogóźno salt dome on the example of the Moszczenica riverbed stretch in Gieczno - Ziułkiewicz, Maciej (Acta Geographica Lodziensia, 2024)
The article presents the results of a study of salinity in the Moszczenica hyporheic zone in the stretch over the Rogóźno salt dome and a review of research hypotheses intended to explain the cause of this peculiar geochemical phenomenon. The economic history of the Rogóźno-Gieczno area does not indicate the existence of a tradition of salt exctraction. These allows us to assume that geogenic salinity, which is evidence of leaching of the salt body and denudation of the gypsum cap, was revealed in the 20th century as a result of geological exploration works. The fact of the presence of saline waters in the immediate vicinity of the riverbed creates a favourable research area for investigating the relations between river and hyporheic waters in the special conditions of wide availability of the chloride ion as the indicator element in the aquatic environment. Annual research did not show a clear relationship between the variability of hydrological and hydrogeological conditions and the condition of the hyporheic zone. However, its provided the basis for distinguishing two zones in the examined part of the riverbed bottom that responded differently to the inflow of saline deep waters. It was assumed that the salinity of the environment around the riverbed was caused by the ascension of saline water from the Jurassic formations which abut to the salt diapir.